Superelastic Behavior of NiTi: Effects of the Stress Level Applied During the Heat Treatment of Cold Worked Wires. (2015) - Soul, H.; Yawny, A.; Wang, X.; Van Humbeeck, J.
Abstract: The effects of the stress level applied during the final straight annealing treatment of cold worked Ni rich NiTi wires (50.8 at% Ni, diameter 50 μm) on the resulting superelastic properties is addressed. Explored parameters were 400 and 500 ˚C for heat treatment temperature, 6, 10 and 30 min for time duration and annealing stresses ranging from 10 to 800 MPa. Heat treated wires were subjected to complete superelastic cycles. Superelastic behavior was characterized by forward / reverse transformation stresses, dissipated energy and residual strain. No significant effect of the stress level on the pseudoelastic stability upon cycling was detected but a remarkable inclination of upper and lower transformation plateaus was obtained for the highest annealing stresses. These results are of particular significance for applications were a more gradual increase of the fraction of transformed material with stress is required, e.g. in proportional actuators.